ANOMALY DETECTION - REVIEW OF METHODS, TOOLS AND ALGORITHMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
This paper contains review of algorithms, methods and tools nowadays used for anomaly detection.Anomaly detection is used in many domains of science and industry, some authors classify anomaly detection as data mining and data science tool, others state it is decision support tool under artificial intelligence domain and indeed the use cases of anomaly detection are very different.The article describes the main algorithms used for anomaly detection from perspective of theory of computer science and practical use cases of anomaly detection in different domains of industry. Several paragraphs are dedicated to the frameworks used by one of the most popular and powerful anomaly detection tools available in the market - Microsoft Anomaly detector.